ANALISIS PENDAPATAN MASYARAKAT DALAM PEMANFAATAN HUTAN TEMBAWANG DI DESA SALUMANG KECAMATAN MEMPAWAH HULU KABUPATEN LANDAK - Rizal, Yose; Lumangkun, Augustine; Husni, Harnani (Universitas Tanjungpura, 2015)
Tembawang forest has the natural resource that used to fulfill the requirement of live society. The aims of this research are to the types of non timber forest product that are extracted by local people in the tembawang area, the amount of revenue in the use of non-timber forest product from tembawang, and to know the factors influence the local people earnings in extractive tembawang. This study used a survey method with interview technique using questionnaires. Sampling of respondents was taken purposive, (purposive sampling). The member of respondents are 50 families in the 3 sub villages of Sempang Ampin, Saba’u, and Batu Pati. The results of this reseach slowed that types of non timber forest product that area extracted are durian, cempedak, keranji, jengkol, kelampai, tampoi, langsat, mangosteen, rambutan, rambai, canary, laugh, petai forest, pehengan, sour of maram, duku, former, acid pauh, sour of kanis, saumang (rambutan), coconut, former / kalimantan, and goods. Besides fruits there is also firewood, bamboo, rebung, for the crop of medicinize like earth dowel, sirih forest, and mengkudu. While the type whic is used as income durian, cempedak, jengkol, and keranji. The are fruits of average of earnings from these fruits is Rp.10.849.860 per family per year, with the highest earnings equal to Rp. 83.254000 per family per year, and the lowest equal to Rp. 779.000 per family per year. The coefficient ditermination is 0,237 means the change of farmer earnings in extracting of forest tembawang that equal to 23,7% is influenced by wide of tembawang area the member of type is influenced the wide area of tembawang, the member of family member working in tembawang, the member of work-hours, and products collected. The regression equation is : Y = 160.951 + 9.724X1 - 045X2 – 12.514X3 – 488X4 + 10.238X5 Keyword : forest, income, people, tembawang, utilizing.